RELIGIOUS LIFE OF KARAKALPAKSTAN IN 1941-1945 (TAMADDUN NURI JURNALI, 2024)
The article talks about the policy of the Soviet government regarding religion and Islam in Karakalpakstan in 1941-1945, the government’s attitude towards religion and religious life during the Second World War.